2018
DOI: 10.1038/s41598-018-23666-y
|View full text |Cite
|
Sign up to set email alerts
|

Schottky model for triboelectric temperature dependence

Abstract: The triboelectric effect, charging by contact, is the working principle in a device called a triboelectric nanogenerator. They are used as efficient energy transducers in energy harvesting. In such generators the charging of surfaces at contact is followed by a separation of the surfaces increasing the electrical energy which can subsequently be used. Different materials have different triboelectric potentials leading to charging at contact. The temperature dependence of the charging has just recently been stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…We also observe that charging of the volcanic sample decreases as the temperature increases. As discussed above, similar behaviors have been noted in nonvolcanic materials by a number of investigators (e.g., Greason, 2000;Lu et al, 2017;Olsen et al, 2018;and Su et al, 2015).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We also observe that charging of the volcanic sample decreases as the temperature increases. As discussed above, similar behaviors have been noted in nonvolcanic materials by a number of investigators (e.g., Greason, 2000;Lu et al, 2017;Olsen et al, 2018;and Su et al, 2015).…”
Section: Resultssupporting
confidence: 74%
“…For example, Greason [2000] found that the magnitude of charge on beads in a vibrated bed decreases with increasing temperature. Additionally, Olsen et al [2018] notes that some researchers (including Wen et al [2014], Su et al [2015], and Lu et al [2017]) report a power output decrease with temperature in triboelectric nano-generators. Temperature variations may also affect the presence of contaminants on surfaces, changing their ability to gain or retain charge [Lowell and Rose-Innes, 1980].…”
Section: Confidential Manuscript Submitted To Journal Of Geophysical Research -Atmospheresmentioning
confidence: 99%
“…and Olsen et al [2018]). Note that the effect of changing humidity is greater than that of changing temperature.…”
Section: Resultsmentioning
confidence: 90%
“…Triboelectric nanogenerators (TENG:s) are used as efficient energy transducers in energy harvesting to replace the need for batteries for small electronic devices 1–4 , or as sensors for different physical properties. For many types of generators containing non-metals the triboelectric charging seems to be done by ion transfer 5,6 or by electron transfer between potential wells of atoms 7 or by both mechanisms. At separation of the surfaces of the generator the so created charge differences induce an electric voltage that contains energy to be harvested.…”
Section: Introductionmentioning
confidence: 99%